Kondisi Belajar dan Pembelajaran (Lima Kategori Kemampuan: Keterampilan Intelektual, Strategi Kognitif, Informasi Verbal, Keterampilan Motorik, dan Sikap) - Fachrani, Anisa; Sari, Renika Indah; R, Risdayanti; S, Saprin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the conditions of learning and instruction as core components of the educational process. Learning is defined as a relatively permanent change in behavior resulting from experience, while instruction refers to the systematic interaction between educators, learners, and learning resources within a specific environment to achieve educational goals. The study uses a qualitative library research method to review educational theories, particularly the perspective of Robert Gagne. Gagne classifies learning outcomes into five categories: intellectual skills, cognitive strategies, verbal information, motor skills, and attitudes. In addition, the study discusses internal and external factors that influence learning and instructional conditions. Understanding these aspects is expected to help educators design more effective and contextual instructional strategies.